Clinical significance of chromatin remodeling factor CHD5 expression in gastric cancer - Hashimoto, Tadayoshi (Oncol Lett, 2020)
Chromodomain helicase DNA-binding 5 (CHD5), which is a member of the CHD family, has been identified as a tumor suppressor gene in a variety of malignancies. The aim of the current study was to clarify the clinical significance of CHD5 expression in gastric cancer. CHD5 expression was evaluated using immunohistochemistry (IHC) in 154 specimens resected from patients with gastric cancer from January 2011 to December 2013, and assessed its relationships with clinicopathological characteristics and survival. In vitro cell proliferation, invasion, and migration assays and western blotting analysis were performed to clarify the role of CHD5 in human gastric cancer cell lines. Of a total of 154 patients, 57 (37.0%) exhibited low CHD5 expression, which was significantly associated with positive lymphatic invasion (P=0.032), advanced pT status (P=0.011), and advanced pStage (P=0.014). Overall survival (OS) in patients with low CHD5 expression was significantly worse compared with patients with high CHD5 expression (hazard ratio, 1.96; 95% confidence interval, 1.09–3.45; log-rank P=0.023). Cox multivariate analysis for OS revealed that CHD5 expression was an independent prognostic factor with age and pN status. In vitro, the upregulation of CHD5 in gastric cancer cells with low CHD5 expression significantly decreased cell proliferation, migration and invasion. CHD5 was associated with the regulation of multiple cancer-related targets, including p53 and enhancer of zeste homolog 2 (EZH2) in western blotting analysis. In conclusion, since CHD5 regulated multiple cancer-related targets, its expression may be a useful prognostic biomarker in patients with gastric cancer.